2020
DOI: 10.3390/en13205267
|View full text |Cite
|
Sign up to set email alerts
|

Emission Measurement of Buses Fueled with Biodiesel Blends during On-Road Testing

Abstract: Increasing the biodiesel content of diesel fuels is encouraged because of its reduced carbon footprint. Pure rapeseed methyl ester (RME)and used cooking oil methyl ester (UCOME) are characterised by well-to-tank greenhouse gas (GHG) reductions of 54% and 88% compared to pure B0 petrodiesel, respectively. Captive fleets such as public transport buses could benefit from these GHG reductions by increasing the biodiesel content of their fuel because they have a consequent yearly fuel consumption. The aim of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Thus, until recently, researchers have been using different techniques to measure on-board the vehicle not only for heavy-duty vehicles (e.g., [35][36][37][38]) but also for light-duty ones (e.g., [39,40]). While research studies with SPN PEMS exist (e.g., [41,42]), the assessment of PEMS is limited. One of the few studies with heavy-duty engines and with three PEMS manufacturers found differences to the 10 nm reference instruments of 50% [22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, until recently, researchers have been using different techniques to measure on-board the vehicle not only for heavy-duty vehicles (e.g., [35][36][37][38]) but also for light-duty ones (e.g., [39,40]). While research studies with SPN PEMS exist (e.g., [41,42]), the assessment of PEMS is limited. One of the few studies with heavy-duty engines and with three PEMS manufacturers found differences to the 10 nm reference instruments of 50% [22].…”
Section: Introductionmentioning
confidence: 99%
“…According to the dierent scenarios, one important aspect to achieve sustainable development is the usage of alternative fuels. They could be energy carriers and electrofuels, 1,2 biofuels such as biodiesel, 3 fuels derived from wastes such as automotive shredder residues 4,5 and other types of molecules such as alcohols. 6 The number of sources of alcohol molecules increases with the development of fermentation and gasication.…”
Section: Introductionmentioning
confidence: 99%